Ethnic variation in Interleukin-6 –174 (g/c) Polymorphism in the Malaysian population - Gan, G.G.; Subramaniam, R.; Lian, L.H.; Nadarajah, V.S. (De Gruyter Open, 2013)

(untitled)
Interleukin-6 (IL-6) is one of the cytokines that has been well studied and implicated in many diseases including cancers. The frequency of the IL-6–174 (G/C) polymorphism had been proven to differ in various populations. Malaysia is a country with three major ethnic populations, Malays, Chinese and Indians. In this study, we proposed to determine the G or C allele frequency of the IL-6 –174 polymorphismin these three populations. A total of 348 blood samples were available for analysis. The median age for the subjects was 31 years. There were a total of 245 males and 103 females. A total of 86 Malays (25.0%), 122 Chinese (33.0%) and 140 Indians (40.0%) were genotyped. The result showed a significant difference in the G or C allele frequency of the –174 polymorphism. The total frequencies for the G and C alleles were 91.0 and 9.0%, respectively. In the Malays, the allele frequency of the C allele was 4.0% compared with 19.0% in the Indians. The C allele was not detected in the Chinese population. This finding is the first reported on the Malaysian population and may be important in determining risk of diseases associated with the IL-6 polymorphism in these three populations.